Who performed this dance move? An exploratory study on the effect of dance individuation on racial bias of Chinese preschoolers in Singapore - Quah, Clarissa Qian Lin (Nanyang Technological University, 2020)
The present study examined the effects of dance individuation training on racial bias in ethnic Chinese 6-year-olds in Singapore (N = 75). Participants were assigned to either the Intervention or Control condition and had their implicit and explicit racial bias measured before and after intervention. In the Intervention condition, participants watched separate videos of four Indian females doing different dance moves each and were instructed to remember each Indian female based on their unique dance move. On the other hand, participants in the Control condition did a filler colouring task for 5 minutes instead of undergoing individuation training. Results showed that there was a significant difference between both conditions in changes of implicit racial bias pre- and post-test. Further analysis showed that participants in the Intervention condition had their implicit racial bias significantly reduced after individuation training, whilst participants in the Control condition did not have significant changes in their implicit racial bias before and after the filler task. Additionally, there was no significant interaction effect between Condition and Timepoint in the analysis for explicit racial bias, whereby participants in both conditions did not have any significant differences in changes of their explicit racial bias before and after intervention. These findings suggest that individuation training specifically targets and reduces implicit racial bias, and that implicit and explicit racial bias are dissociated from each other. These findings have implications on moral education in Singapore preschools, specifically on maintaining racial harmony in Singapore.